Concordium 2016: Data and Knowledge Transforming Health. Issue 2 (20th April 2017) - Devine, Beth
Introduction and Context: Concordium 2016 celebrated the potential for data and knowledge to transform health. Through a series of plenaries, presentations, workshops and demonstrations, the conference highlighted projects among four themes: effectiveness and outcomes research, health care analytics and operations, public and population health, and quality improvement. Papers in the Special Issue: The eight papers that comprise this special issue of eGEMs provide exemplars of solutions to the Big Data problems faced in today's healthcare environment. Cross-Cutting Elements and Overlapping Themes: Several of the papers contain elements of multiple overlapping themes. We integrate these into five overlapping themes: telehealth, user-centered design/usability, clinic workflow, patient-centered care, and population health management through prediction modeling and risk adjustment. Conclusion and Future Directions: The effort to leverage all types of Big Data to improve health and healthcare is a monumental effort that will require the work of numerous stakeholders, and one that will unfold incrementally over time. This collection of eight papers reflects the current state of the art. Concordium 2017 will take a different form, inviting a small set of leaders in the field to focus on the next round of exciting and provocative research currently underway to improve the nation's health.